(untitled) (Journal of Misan Researches, 2022)
This study aims to show the effect of the textual casting in Surat Al-Adiyat on the recipient, as casting is one of the seven textual criteria set by (Bogrand) to find out whether the text that meets those criteria to achieve the textuality or not. The large number of studies and research that have been written on the interpretation of Surat Al-Adiyat has called us to reduce research on this matter. In order to avoid repetition, in addition to the fact that the researcher did not neglect this topic, rather he relied upon many of his textual analyzes on what was stated in the interpretation of the surah, so; We devoted the preface to the study of the major structure of the surah (Al-Adiyat). The research was divided into two sections, as the first topic included a theoretical introduction to grammatical casting, textual standards, casting for the ancients, casting for modernists, and means of casting. Because it is closer to the subject of our study. In the second topic, I dealt with the application of the casting criterion to Surat Al-Adiyat. Then we concluded our study, including the most important findings of this study, with a list of the sources and references that it relied on.